The Impact Of The Visa Exemption Policy On International Tourist Arrivals And Local Craft Trade In Indonesia - Mawardi Kartasasmita; Khoirunurrofik Khoirunurrofik (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The Visa Exemption Policy is a strategic measure aimed at increasing international tourist arrivals and fostering economic growth. This study examines the impact of the visa exemption policy on international tourist arrivals and local craft trade by utilizing panel data from 34 provinces in Indonesia over the period 2013–2023. The analysis employs a fixed effects model initially and an Ordinary Least Squares (OLS) approach with year-fixed effects subsequently. The regression results indicate that, on average, granting visa exemptions to an additional country leads to a 0.4% increase in international tourist arrivals. In the second model, a 1% increase in the number of international tourists contributes to a 0.492% rise in the Gross Regional Domestic Product (GRDP) of the local craft sector. The Sobel test further confirms that international tourist arrivals significantly mediate the relationship between the Visa Exemption Policy and local craft trade, with a z-value of 5.36. These findings suggest that the Visa Exemption Policy has a significant positive impact on local craft trade in Indonesia, albeit indirectly, through the mediation of increased international tourist arrivals.